Evaluation of the Use of the Merdeka Mengajar Platform at Petir 4 Public Elementary School, Tangerang City - Ayuningrum, Ayuningrum; Yuhana, Yuyu; Leksono, Suroso Mukti (FKIP - Universitas Riau, 2025)
The researcher wants to evaluate the use of the Merdeka Mengajar platform at SDN Petir 4, Tangerang City, which is useful for helping to improve the quality of learning. In this study, the data collection method will involve surveys of teachers and students, observations during learning practices using the Merdeka Mengajar Platform (PMM), and analysis of student learning outcomes from assessments carried out before and after the implementation of the Merdeka Mengajar Platform (PMM). The results of the study consistently show that most teachers admit that PMM is very helpful for them in preparing innovative lesson plans, understanding the essence of the Merdeka Curriculum better, and ultimately improving the quality of learning in the classroom. This study concludes that the use of the Merdeka Mengajar Platform Merdeka Mengajar Platform (PMM) at SDN Petir 4 has shown a significant positive impact in several crucial aspects. However, identification of the remaining implementation challenges is also a major focus, which requires further attention for program optimization.